2008
DOI: 10.1158/0008-5472.can-07-1182
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Phosphatase Activity of PTEN Regulates Src Family Kinases and Controls Glioma Migration

Abstract: Phosphatase and tensin homologue deleted on chromosome 10 (PTEN) is mutated or lost in 60% to 70% of advanced gliomas and is associated with malignant phenotypic changes such as migration, which contribute to the morbidity and mortality of this disease. Most of the tumor suppressor function of PTEN has been attributed to its ability to dephosphorylate the second messenger, phosphatidylinositol 3,4,5-triphosphate, resulting in the biological control of the phosphatidylinositol 3-kinase (PI3K)/AKT pathway. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(139 citation statements)
references
References 49 publications
10
125
2
1
Order By: Relevance
“…This activity is associated with inhibition of invasion in glioma cells and more recently has been shown to increase sensitivity to ErbB2 inhibition by trastuzumab in breast cancer cells (2,39), but it is unclear as to which signals may determine the outcome of the PTEN-SFK interaction. By invoking FGFR as an additional input into PTEN phosphorylation, our data may help to explain how this reciprocal interaction can be regulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity is associated with inhibition of invasion in glioma cells and more recently has been shown to increase sensitivity to ErbB2 inhibition by trastuzumab in breast cancer cells (2,39), but it is unclear as to which signals may determine the outcome of the PTEN-SFK interaction. By invoking FGFR as an additional input into PTEN phosphorylation, our data may help to explain how this reciprocal interaction can be regulated.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years it has become clear that PTEN also performs a number of tumor suppressor functions independent of its lipid phosphatase activity, including the suppression of cell migration, maintenance of genomic stability, and inhibition of cell cycle progression (2)(3)(4)(5). The PTEN gene is lost or mutated in ∼40% of glioblastoma multiforme (GBM) (6,7), and retention of PTEN protein expression has been linked with responses to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in GBM patients (8,9), suggesting that the detection of functional PTEN may inform the successful deployment of targeted therapeutics in this currently intractable disease.…”
mentioning
confidence: 99%
“…[92] PTEN controls integrin-dependent migration through the regulation of Src family kinase activation, in a PI3K/AKT-independent manner. [93] The re-expression of PTEN in GBM cell lines increases the cellular content and activity of the p53 tumor suppressor protein inducing cell cycle arrest and increasing the sensitivity of the tumor cells to various chemotherapeutic agents such as etoposide. [94] Upstream regulators of EMT induction, such as insulin-like growth Factor-1 receptor (IGF-1R), c-MET and the CXCR4 receptor, have been proposed as potential targets to inhibit GBM or MB invasion.…”
Section: Emt Cell Invasion and Motilitymentioning
confidence: 99%
“…It is possible that the effects of PTEN on cell migration in vitro are dependent on experimental conditions. Indeed, studies suggesting that the lipid phosphatase activity of PTEN regulates migration by RAC1 inhibition were performed on fibronectin and mediated by a 5 b 1 integrin (Liliental et al, 2000); however, Dey et al (2008) studied glioma cell migration on vitronectin, which binds a v b 3 integrin, and showed that PTEN's protein phosphatase activity negatively regulated RAC1 indirectly by regulating the activity of the SRC-family kinase, FYN. It has also been suggested that PTEN may regulate cell migration by directly dephosphorylating FAK in the DBTRG-05MG glioblastoma cell line (Tamura et al, 1998); however, other studies have shown that PTEN does not influence FAK phosphorylation in other cell lines (Maier et al, 1999;Jones et al, 2001).…”
Section: Migration and Invasionmentioning
confidence: 99%